Diverse Protein Profiles in CNS Myeloid Cells and CNS Tissue From Lipopolysaccharide- and Vehicle-Injected APPSWE/PS1ΔE9 Transgenic Mice Implicate Cathepsin Z in Alzheimer’s Disease - Thygesen, Camilla; Ilkjær, Laura; Kempf, Stefan J.; Hemdrup, Anne Louise; von Linstow, Christian Ulrich; Babcock, Alicia A.; Darvesh, Sultan; Larsen, Martin R.; Finsen, Bente (Frontiers in Cellular Neuroscience, 2018)
Neuroinflammation characterized by chronic activation of the myeloid-derived microglia is a hallmark of Alzheimer’s disease (AD). Systemic inflammation, typically resulting from infection, has been linked to the progression of AD due to exacerbation of the chronic microglial reaction. However, the mechanism and the consequences of this exacerbation are largely unknown. Here, we mimicked systemic inflammation in AD with weekly intraperitoneal (i.p.) injections of APPSWE/PS1DE9 transgenic mice with E. coli lipopolysaccharide (LPS) from nine to twelve months of age, corresponding to the period with the steepest increase in amyloid pathology. We found that the repeated LPS injections ameliorated amyloid pathology in the neocortex while increasing the neuroinflammatory reaction. To elucidate mechanisms, we analyzed the proteome of the hippocampus from the same mice as well as in unique samples of CNS myeloid cells. The repeated LPS injections stimulated protein pathways of the complement system, retinoid receptor activation and oxidative stress. CNS myeloid cells from transgenic mice showed enrichment in pathways of amyloid beta clearance and elevated levels of the lysosomal protease cathepsin Z, as well as amyloid precursor protein, apolipoprotein E and clusterin. These proteins were found elevated in the proteome of both LPS and vehicle injected transgenics, and co-localized to CD11b+ microglia in transgenic mice and in primary murine microglia. Additionally, cathepsin Z, amyloid precursor protein, and apolipoprotein E appeared associated with amyloid plaques in neocortex of AD cases. Interestingly, cathepsin Z was expressed in microglial-like cells and co-localized to CD68+ microglial lysosomes in AD cases, and it was expressed in perivascular cells in AD and control cases. Taken together, our results implicate systemic LPS administration in ameliorating amyloid pathology in early-to-mid stage disease in the APPSWE/PS1DE9 mouse and attract attention to the potential disease involvement of cathepsin Z expressed in CNS myeloid cells in AD.